1986
DOI: 10.1523/jneurosci.06-06-01583.1986
|View full text |Cite
|
Sign up to set email alerts
|

Multielectrode analysis of coordinated, multisite, rhythmic bursting in cultured CNS monolayer networks

Abstract: Laser-deinsulated, printed-circuit electrodes integrated into the floor of culture chambers have been used to monitor the spontaneous activity of mouse spinal monolayer cell cultures. This technique has allowed a multisite analysis of activity over long periods of time in closed chambers. In 63 cultures investigated 3-5 weeks after seeding, 89% included single- or multiunit bursting. Based on a subset of 40 cultures in which all electrodes were sequentially scanned, bursting was found on 41% of the active elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 34 publications
(38 reference statements)
0
50
0
Order By: Relevance
“…As the MEA technology can be applied to any electrogenic tissue, that is, central and peripheral neurons, heart cells, and muscle cells [12,14,18,24,25,26,27,28,29,30,31], the MEA biosensor is an ideal in vitro system to monitor both acute and chronic effects of drugs and toxins and to perform functional studies under physiological or induced pathophysiological conditions that mimic in vivo damage. By recording the electrical response of various locations on a tissue, a spatial map of drug effects at different sites can be generated which provides important clues about a drug's specificity.…”
Section: Recording Of Field Potentials In Cell and Tissue Culturesmentioning
confidence: 99%
“…As the MEA technology can be applied to any electrogenic tissue, that is, central and peripheral neurons, heart cells, and muscle cells [12,14,18,24,25,26,27,28,29,30,31], the MEA biosensor is an ideal in vitro system to monitor both acute and chronic effects of drugs and toxins and to perform functional studies under physiological or induced pathophysiological conditions that mimic in vivo damage. By recording the electrical response of various locations on a tissue, a spatial map of drug effects at different sites can be generated which provides important clues about a drug's specificity.…”
Section: Recording Of Field Potentials In Cell and Tissue Culturesmentioning
confidence: 99%
“…Such cultures retain many morphological, pharmacological, and electrical properties of cortical networks in vivo (Dichter, 1978) and allow much more detailed observation and manipulation than intact brains, at the molecular, cellular, and network levels (Droge et al, 1986;Emery et al, 1991;Curtis et al, 1992;Wilkinson, 1993;Bove et al, 1994Bove et al, , 1997Rhoades et al, 1996;Canepari et al, 1997;Gross et al, 1997;Liu et al, 1997;Harsch et al, 1998;Honma et al, 1998;Jimbo et al, 1998Jimbo et al, , 1999Turrigiano, 1999;Harsch and Robinson, 2000;Zhu et al, 2000;Keefer et al, 2001;Streit et al, 2001;Shahaf and Marom, 2001;Corner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this manuscript we perform an extensive quantitative analysis of patterns of network burst initiation in cortical neural networks in vitro. These spontaneous collective high frequency action potential discharges are major features of such systems [2, 8,10,18,19,23,24,[36][37][38] and can influence learning and information processing by changing synaptic properties [1,5]. Previous theoretical and experimental research showed that multiple ignition sites, sometimes termed initiation loci [24], privileged neurons [11], and even initiation zones [12], create network bursts by recruiting constituent neurons.…”
Section: Introductionmentioning
confidence: 99%